Ceftolozane-tazobactam activity against clinical isolates of Pseudomonas aeruginosa from ICU patients with pneumonia: United States, 2015–2018. (November 2021) - Pfaller, Michael A.; Shortridge, Dee; Harris, Kelly A.; Garrison, Mark W.; DeRyke, C. Andrew; DePestel, Daryl D.; Moise, Pamela A.; Sader, Helio S.
Highlights: The susceptibility of 781 Pseudomonas aeruginosa isolates collected from US patients was analysed. Intensive care unit patients with confirmed or suspected P. aeruginosa pneumonia were included. Ceftolozane-tazobactam (C/T) was the most active agent (97.2% susceptible). C/T remained >85% active against  P. aeruginosa  that were non-susceptible to empiric β-lactams. Conversely, other common β-lactams retained <45% susceptibility in this scenario. ABSTRACT: Objectives: To report on the activity of ceftolozane-tazobactam and comparators against Pseudomonas aeruginosa isolates collected from hospitalized patients with pneumonia in US intensive care units (ICUs) between 2015 and 2018. Activity against all P. aeruginosa and common resistant phenotypes are described to better inform decision-making and support antimicrobial stewardship efforts. Methods: In total, 781 P. aeruginosa isolates were collected from 28 US hospitals. These isolates were tested for susceptibility to ceftolozane-tazobactam and comparators by Clinical and Laboratory Standards Institute (CLSI) broth microdilution methodology using CLSI (2020) breakpoints. Phenotypes analysed included piperacillin-tazobactam-non-susceptible (NS), cefepime-NS, ceftazidime-NS, meropenem-NS and difficult-to-treat resistance (DTR). Results: Ceftolozane-tazobactam was the most potent agent tested (minimum inhibitory concentration to inhibit 50% and 90% of isolates of 0.5 and 2 mg/L, respectively, inhibiting 97.2% at the susceptible breakpoint of ≤4 mg/L). Traditional first-line antipseudomonal β-lactam antibiotics (piperacillin-tazobactam, cefepime and ceftazidime) demonstrated <33% susceptibility when P. aeruginosa was NS to one or more agent. Although escalation of therapy to meropenem is commonly employed clinically, meropenem susceptibility ranged from 33.6% to 44.9% if P. aeruginosa was NS to any traditional first-line antipseudomonal β-lactam agent. Conversely, ceftolozane-tazobactam remained active against isolates that were NS to other agents, inhibiting 88.4% of isolates NS to piperacillin-tazobactam, 85.0% of isolates NS to cefepime and ceftazidime, and 90.3% of isolates NS to meropenem. Ceftolozane-tazobactam also maintained activity against 73.0% of DTR isolates. Conclusions: Ceftolozane-tazobactam maintained high activity against P. aeruginosa isolated from hospitalized patients with pneumonia in US ICUs, and had the greatest activity against isolates NS to one or more antipseudomonal β-lactams and DTR isolates.